OUTCOMES OF PERCUTANEOUS NEPHROLITHOTOMY IN ELDER AGE PATIENTS-SINGLE CENTER EXPERIENCE - Iqbal, Nadeem; Iqbal, Sajid; Hasan, Aisha; Majeed, Mehr; Iqbal, Daud; Shahzad, Mahrukh; Khan, Faheemullah; Khawaja, Muhammad Athar; Akhter, Saeed (Journal of Ayub Medical College Abbottabad, 2021)
Background: Urolithiasis is a prevailing ailment affecting all age groups across global population. In modern innovative industry endoscopic instruments alterations and miniaturization has simplified the interventional strategy for undertaking these procedures for renal stones. However, there has been paucity of studies regarding outcomes of Percutaneous Nephrolithotomy (PCNL) in elder age group. We aimed to report success rates and complications in elder age group. Methods: This was a retrospective review of the charts for subjects that underwent unilateral PCNL from 2012 till 2018 November at a tertiary care hospital at capital of Pakistan. Patients of age ‰¥60 years were chosen for this study. PCNL procedures were done in prone position. We implemented the Guy stone scoring (stone complexity) to forecast the net results of PCNL. Information regarding variables were recorded in specified proforma and then processed in SPSS version 16 for the statistical computations. Results: On the whole 79 patients were incorporated for this study. Most common presenting complaint in clinic was flank pain followed by haematuria and fever respectively. Mean age in this analysis was calculated as 63.36±5.19 years. Mean size for calculi was 449±163mm2. One patient underwent transfusion after surgery while only 2.5% of these patients had sepsis (post PCNL procedure). Stone free rate was significantly affected by Guys stone score (GSS). Conclusion: PCNL can be undertaken safely and effectually for achieving treatment goals even in elder subjects. Stone free rates are higher in lower Guys stone score as compared to the higher scores.